EFEKTIVITAS HIPOFISA AYAM BROILER TERHADAP RESPON OVULASI IKAN BETOK (Anabas testudeineus, Bloch) - Andre Wijaya; Muhammad Sugihartono; Muarofah Ghofur (Universitas Batangahari Jambi, 2022)
Betok fish (Anabas testudineus, Bloch) is a local freshwater fish that has high economic value and is loved by the community, but has not been widely cultivated, because the betok fish have not been bred so that fish production still relies on catches from nature. The potential for betok fish to become consumption fish and ornamental fish is accompanied by increasing market demand for Violita et al (2019). This study aims to determine the effect of the effectiveness of the broiler's pituitary gland on the ovulatory response of betok fish (A. testudeineus, Bloch) by using a hormone extract from the broiler's pituitary gland. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. Where each treatment was given an injection dose: Treatment A: Hypophysis Broiler Chicken 0.2 ml/kg. Treatment B : Hypophysis of Broiler Chicken 0.4 ml/kg. C : Hypophysis Broiler Chicken 0.6 ml/kg. Treatment D : Control. Parameters Observed Ovulation Latency Time, fecundity. Research shows that the average latency time is 8.07 hours. 6518 items.